An Assessment on The Role of Cryptocurrency in Modern Kidnapping for Ransom Cases in Cities of Pasay and Paranaque - Desamito Jr.,, Marceliano A.; Bautista III, Leonardol O.; Dela Cruz, Loreta R.; Garcia, Moises B.; Tomas Jr, Cecilio G.; Villa, Elizabeth Buena; Mobo, Froilan D.; Golla, Nathaniel S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study aimed to address the influence of cryptocurrency on contemporary kidnapping for ransom in the cities of Pasay and Paraňaque as assessed by anti-kidnapping group personnel towards the development of a strategic proposal to combat kid-napping in the digital landscape.This research employed a quantitative-descriptive methodol-ogy, utilizing stratified random sampling as the research design to carefully select respondents from the PNP office Anti-Kidnapping Group. A total of twenty (20) survey questionnaires will be distributed to gather data on the evaluation of PNP per-sonnel regarding the role of cryptocurrencies in contemporary kidnapping for ransom, particularly in relation to investigation, negotiation, and operations. The study's findings indicate that: The Philippine National Police Anti-Kidnapping Group (AKG) should improve educational programs and strategies to address kidnapping for ransom. Mandatory training on proposed initia-tives will be necessary for the PNP AKG. Additionally, the PNP AKG will oversee security in Pasay and Paranaque, and the BSP is actively monitoring developments in virtual currency, particular-ly regarding their potential use in money laundering and other illicit activities, and will take appropriate action as needed. The findings emphasized that strong regulation, including the Anti-Fraudulent Activities in Financial Accounts Act (AFASA) and the suggested amendments to the Bank Secrecy Act, are es-sential and long overdue. The BSP and other regulatory authori-ties in the Philippines must actively oversee cryptocurrencies. Furthermore, the PNP AKG and ACG necessitate revised tech-niques to proficiently obstruct blockchain technology from ena-bling cross-border bitcoin transactions.